2018
DOI: 10.1089/g4h.2017.0038
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function Computerized Training in Very Preterm-Born Children: A Pilot Study

Abstract: BrainGame Brian is a feasible intervention for very preterm-born children with attention problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, this literature is based on solely training working memory, while other executive functions, such as inhibitory control and cognitive flexibility, are also impaired in this population and may benefit from computerized interventions. Given the fact that executive function remains a vulnerable area of cognitive function in the population born preterm, future studies should be conducted on which type of interventions may be effective to diminish the encountered difficulties in executive function …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this literature is based on solely training working memory, while other executive functions, such as inhibitory control and cognitive flexibility, are also impaired in this population and may benefit from computerized interventions. Given the fact that executive function remains a vulnerable area of cognitive function in the population born preterm, future studies should be conducted on which type of interventions may be effective to diminish the encountered difficulties in executive function …”
Section: Discussionmentioning
confidence: 99%
“…Aarnoudse-Moens et al 103 Anderson et al 104 Brumgaugh et al 105 Crotty et al 90 Delande et al 107 Wong et al 111 Rose et al 24 Murray et al 110 Hodel et al 62 Hitzert et al 109 Giordano et al 108 Cserjesi et al 105 Mulder et al 18…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions mostly focus on the home environment, parent-infant relationships, and parenting skills, but few focus on infant development alone. Computerised cognitive training programmes have been tested among pre-and school-age children who were born before term [1,49], but not with younger preterm children. Furthermore, few studies have reported on the use of eye-tracking methods to examine preterm infants' attention abilities [21,36,59,66].…”
Section: Aims Of the Studymentioning
confidence: 99%
“…Several studies have been conducted in the last few years to test the contribution of early intervention on the development of EFs (Liu et al, 2015;Traverso et al, 2015;Howard et al, 2018;Zhang et al, 2019). Other studies have explored the efficacy of ad hoc EF training programs (Kronenberger et al, 2011;Espinet et al, 2013;Grunewaldt et al, 2013;Hardy et al, 2016;Aarnoudse-Moens et al, 2018;Boivin et al, 2019;Zhang et al, 2019). For a review of intervention programs, see Diamond and Ling (2019).…”
Section: Introductionmentioning
confidence: 99%